Syntheses of Fawcettimine-Type Lycopodium Alkaloids Utilizing the Pauson–Khand Reaction - Nakayama, Atsushi; Kitajima, Mariko; Takayama, Hiromitsu (Synlett, 2012)
The asymmetric total syntheses of some fawcettimine-type Lycopodium alkaloids, utilizing an intramolecular Pauson–Khand reaction as the key step, are described.1 Introduction2 First Asymmetric Total Syntheses of Lycoposerramine-C and Phlegmariurine A3 First Asymmetric Total Synthesis of Huperzine Q4 Total Syntheses of Fawcettimine and Fawcettidine5 Conclusion
Keywords: alkaloids; total synthesis; asymmetric synthesis; fawcettimine; Pauson–Khand reaction